Does Youth Baseball Result in Morphologic Changes of the Lateral Elbow? A Prospective MRI Study - Harkin, William E. (Clin Orthop Relat Res, 2021)
BACKGROUND: Stress from overhead throwing results in morphologic changes to the shoulder in youth baseball players. With greater valgus torque stresses, the elbow experiences injuries specifically attributed to throwing. However, no previous work that we know of has assessed throwing-related morphologic changes of the elbow without associated conditions. QUESTIONS/PURPOSES: (1) Do children who play competitive baseball have enlargement or overgrowth of their radial head shape and/or capitellum compared with the nondominant elbow on MRI? (2) Do children who stop playing year-round baseball have less enlargement of the lateral elbow structures than children who maintain a high level of play? METHODS: A prospective study was conducted between 2015 and 2018 on preadolescent boys who underwent voluntary MRI of their bilateral elbows before the start of the spring baseball season. Twenty-six children agreed to participate out of a four-team league that was asked to participate; their first MRI was obtained at a mean (range) age of 12 years (10 to 13). We also obtained their history related to throwing and performed a physical examination. Players had a mean of 5.6 years of playing before their first MRI, and half the children (13 of 26) were year-round baseball players. Sixty-two percent (16 of 26) reported being either or both a pitcher or catcher as their primary position. No child was excluded from participation. Three years later, these boys were asked to return for repeat MRI and physical examinations. Fifty-eight percent (15 of 26) of players were still playing at the 3-year MRI. Continued play or new onset of pain was documented. Radiographic measurements were then compared between dominant and nondominant arms, and the differences of these changes were compared between those who had continued playing during the study period and those who had quit. The measurements were made in all three planes of the radial head and capitellum, both osseous and cartilaginous. Measurement intrarater and interrater reliability were in the good-to-excellent range (intraclass correlation coefficient 0.77 to 0.98). RESULTS: When we compared dominant and nondominant arms, we found there was no dominant arm overgrowth (difference between baseline and 3-year measurements) in any measurement; for example, sagittal capitellum measurements in dominant arms were 2.5 ± 1.1 mm versus non-dominant arms: 2.8 ± 1.1 mm (mean difference -0.23 [95% CI -0.55 to 0.08]; p = 0.13). There was only undergrowth of the cartilaginous axial diameter of the radial head (change in dominant: 2.5 ± 1.3 mm; change in nondominant: 3.2 ± 1.7 mm; mean difference -0.64 mm [95% CI -1.2 to -0.06]; p = 0.03). There was no enlargement of the lateral elbow structures when children who continued to play were compared with children who stopped playing; for example, the difference in the bone-only growth ratio of the sagittal radial head to humerus of those still playing was 0.001 ± 0.03 and it was 0.01 ± 0.03 for those not playing (mean difference -0.01 [95% CI -0.04 to 0.01]; p = 0.29). CONCLUSION: In healthy children who play baseball for multiple years between the ages of 6 to 11 years, continued torque at the elbow from throwing does not result in morphologic changes as it does in the shoulder. Despite evidence that injuries and surgery because of long-term participation in a throwing sport results in a larger radial head and capitellum, our study presents evidence that outside an injured elbow, throwing alone does not appear to change the morphology of the lateral elbow. Therefore, changes to the radial head size could presuppose other elbow pathology and future study could be performed to better evaluate the correlation. LEVEL OF EVIDENCE: Level I, prognostic study.